Total Seepage Resistance Model of Water-Displacing Diffusion of Slurry in Series and Parallel Fractures. (30th January 2022) - Hu, Yang; Xie, Junhe; Ge, Jian; Liu, Gang
Abstract : With the increase in mining depth, potential water inrush in the limestone-fractured aquifers of Taiyuan formation and Ordovician formation becomes seriously threatened to the mining process. Grouting reinforcement, as a common prevention method, has been widely used in mine water inrush prevention. In this paper, a model of "seepage resistance" is proposed for the slurry diffusion in a single fracture and the theoretical expression on the seepage resistance corresponding to slurry with different flow patterns is conducted. The total seepage resistance model of water-displacing diffusion by slurry in series and parallel fractures is established. With the Lagrange interfacial tracing method, the control equations of water-displacing diffusion by slurry in fracture networks are derived, which get mutually validated with the theoretical results.